Neurological complications in subjects with sickle cell disease or trait in Mali - Landouré, Guida (Glob Heart, 2017)
BACKGROUND: Sickle cell disease (SCD) is the most common inherited disorder in the world. Although more common in Africa, the clinical care of patients with this disease is still a problem in this part of the world. Sickle cell disease is characterized by a wide range of complications, but neurological features are not understood by health practitioners. OBJECTIVES: The goal of this study is to clinically characterize patients with SCD or trait (SCT) who presented neurological complications and to explore the underlying causes. METHODS: Patients with SCD or SCT who presented neurological features were seen in our neurology clinic. Brain CT-scans were performed to confirm cerebral lesions. EEG and EMG were also performed where needed. Blood cell count and CK levels were done. RESULTS: Eight patients with SCD or SCT presented neurological symptoms. Stroke was the most seen neurological complications with six cases (85%), and the remaining patients had myopathy. Two of the patients with stroke presented with seizures later in the disease course. The diagnosis of stroke was based on clinical findings and/or brain imaging, and for myopathy on the presence of proximal weakness and high CK levels. When available, patients always had low hemoglobin levels (8–11 g/dl). In addition, patients with myopathy had high CK levels. CONCLUSION: complications of SCD or SCT are frequent, especially in Africa because of limited access to specialized care. Although stroke is the most reported neurological complication, myopathy needs more attention. This study sets the field for larger cohort studies that may come up with standardized approaches to prevent complications in resource limited countries.